Human endogenous retroviruses and exogenous viral infections - Bao, Chenxuan; Gao, Qing; Xiang, Huayuan; Shen, Yuxuan; Chen, Qiaoqiao; Gao, Qianqian; Cao, Yuanfei; Zhang, Mengyu; He, Wenyuan; Mao, Lingxiang (Frontiers in Cellular and Infection Microbiology, 2024)
The human genome harbors many endogenous retroviral elements, known as human endogenous retroviruses (HERVs), which have been integrated into the genome during evolution due to infections by exogenous retroviruses. Accounting for up to 8% of the human genome, HERVs are tightly regulated by the host and are implicated in various physiological and pathological processes. Aberrant expression of HERVs has been observed in numerous studies on exogenous viral infections. In this review, we focus on elucidating the potential roles of HERVs during various exogenous viral infections and further discuss their implications in antiviral immunity.